Best practice of framing and communicating school goals by principals of cluster secondary schools Malaysia: perceptions of principals, teacher-administrators and teachers - Salleh, Mohamad Johdi (2012)
The Ministry of Education Malaysia launched the implementation of cluster secondary schools aim to develop and produce excellent students in the curriculum and co-curriculum. The achievement of the students is in the full power and authority of the principal primarily through the effective function of defining the school mission. Hence, the purpose of the study is to examine the practice of framing and communicating school goals by the principals of the Cluster Secondary Schools, Malaysia as perceived by 418 respondents comprises of 12 Principals, 120 Teacher-Administrators, and, 286 Teachers of selected cluster secondary schools in Malaysia. The study used questionnaire as a mean of data collection. The data was analyzed by SPSS version 17.0 and presented in frequency and mean. The findings of the study indicate that the ‘use of data on student academic performance’ were highly used when framing school goals with highest mean score 4.26 and its standard deviation standing at 0.808. The findings also show that the highest score on communicating schools goals was item ‘discuss the school's academic goals with teachers at faculty meetings’ with mean 4.21 and standard deviation 0.839. It is clear that the finding is very significant to the success implementation of cluster secondary schools in developing and producing excellent students who are nationally and internationally competence and accepted to pursue studies in the world prestigious universities.